Enhancing brand awareness via halal brand personality - Ramdzan Ali, Al Amirul Eimer; Razali, Khairil Azwar; Othman, Abdul Kadir (International Institute for Halal Research and Training (INHART), 2021)
This paper develops the concept of the halal brand personally dimensions introduced by Ahmad which consists of (i) purity, (ii) excitement, (iii) sophistication, (iv) safety and (iv) righteousness on brand awareness. The concept of halal brand personality is vital for service providers to create an awareness about their products and services in the consumers’ mind as this could be the catalyst for service providers to achieve sustainable competitive advantage (SCA). This is because the five factors that contribute to the halal brand personality are being regarded to be an assurance for halal products and services. It symbolizes the value that are not just for Muslims, but for non-Muslims as well. The concept of halal brand personality will assist the marketers, service providers to convince the customers that the products offered are safe and high in quality.